The relationship between ruminal mat consistency of calves and mortality or immunity - Shinsuke Abe; Kazuho Suzuki; Yosuke Sasaki; Masahiro Yasuda (Scientific Reports)
Abstract Two studies were conducted on the relationship between ruminal mat consistency (RMC) and (1) calf mortality or (2) immunity. Assessment of RMC was by ten repeated manual compressions of the middle rumen; good-RMC showed no fluid bounce-back (FBB), while poor-RMC showed FBB. The first study examined whether RMC affected calf mortality. Monthly feeding management guidance (FMG) was implemented for 5 years on a commercial farm with Holstein–Friesian × Japanese black calves, directing increased forage consumption for poor-RMC calves aged 50–180 days. Compared to 35 control farms, the FMG period showed significantly lower total mortality (3.8% vs. 0.8%, P < 0.001, OR = 4.7) and lower respiratory mortality (2.3% vs. 0.1%, P < 0.001, OR = 18.3). The second study tested the hypothesis that RMC affects calf immunity. Peripheral blood of good-RMC (n = 6) and poor-RMC (n = 6) calves was compared. Good-RMC showed higher phagocytosis in monocytes (P = 0.05, r = 0.63) and granulocytes (P = 0.02, r = 0.78), and higher numbers of CD4 + (P = 0.07, r = 0.58), CD8 + (P = 0.07, r = 0.60), and B-cells (P = 0.03, r = 0.62). In mRNA expression, good-RMC showed lower TNF-α (P = 0.02, r = 0.70), IL-1 (P = 0.09, r = 0.49), IL-12 (P = 0.04, r = 0.59) and IL-10 (P = 0.13, r = 0.44), and higher IL-16 (P = 0.07, r = 0.53) compared to poor-RMC. These results suggest that RMC affects calf mortality and immunity, emphasizing the importance of feeding management in improving sustainability.